An efficient lumped mass model for seismic response analysis of triple-layer seismic isolation super high-rise structures - Yuan Zhang; Qi Luo; Liulei Lu; Qionglin Fu; Dewen Liu; Junfeng Wang; Feng Xing (Soil Dynamics and Earthquake Engineering, 2026)

A novel unified distance potential-based contact framework for NMM–MPM simulation of landslide–structure interaction - Junfeng Li; Xiaodong Fu; Hangtian Song; Yang Xia; Yongtao Yang (Computers and Geotechnics, 2026)

Numerical exploration of structural-jointed rock slope using a NCDDAM with random-field workflow - Hangtian Song; Xiaodong Fu; Junfeng Li; Yang Xia; Yongtao Yang (Computers and Geotechnics, 2026)

Unveiling the pathogenesis and therapeutic strategies of Alzheimer’s disease through cuproptosis - Shuangfeng Xu; Jing Mu; Zhifeng Wang; Jiao Yang; Daman Tian; Ting Shi; Junfeng Lan; Pengfen He; Zhihui Hao; Youchuan Fu; Liwei Xing; Jianzhou Ye; et al. (BioMetals, 2026)

Investigation of high-performance proton exchange membrane fuel cells with integrated bipolar/gas diffusion layer structures: Effects of porosity gradient in tetradecahedral lattice flow field on mass transfer and electrochemical reactions - Qingshan Liu; Lixin Chen; Jiakun Si; Kexin Peng; Xiaojing Wang; Geng Luo; Pei Fu; Yong Zhang; Junfeng Wang; Yisong Chen (Chemical Engineering Journal, 2026)

D–A–A engineered covalent organic frameworks for photocatalytic degradation of microcystin-LR and inactivation of Microcystis aeruginosa - Niao Fu; Qingzhi Liu; Ya Zou; Yujiao Liu; Anzhong Peng; Vadim Popkov; Junfeng Li; Kezhen Qi; Jieli He (Chemical Engineering Journal, 2026)

Hyperspectral model for evaluating nitrogen requirements of high-quality indica fragrant rice in South China using the critical nitrogen concentration dilution curve - Yufen Zhang; Feifei Zhu; Zhaowen Mo; Kaiming Liang; Zhanhua Lu; Yibo Chen; Junfeng Pan; Xiangyu Hu; Rui Hu; Meijuan Li; Xinyu Wang; Songpo Duan; et al. (Plant and Soil, 2026)

Deciphering the crack and pore self-healing effects of sustainable eco-friendly bio-mortar under coastal zone multi-interfaces - Qionglin Fu; Siyu Liu; Peng Dai; Wei Zeng; Junfeng Wang (Frontiers in Marine Science, 2026)
Coastal concrete structures support coastal element cycling and ecosystem services, but cracks from corrosion, loading, and wet-dry cycles threaten safety and disrupt nearshore biogeochemical cycles. Microbially Induced Calcium Carbonate Precipitation (MICP) represents a promising low-carbon strategy for autonomous crack healing; yet, its efficacy and mechanisms within these complex coastal environments remain elusive. Herein, the zonal self-healing performance of MICP across atmospheric, tidal, and submerged zones was evaluated using marine-origin Bacillus subtilis (BS)-based mortar (BSM) and Sporosarcina pasteurii (BP)-based mortar (BPM), with ordinary mortar (OM) serving as a control. Results indicate that the marine environment exerts a distinct zonal regulation on healing efficiency. The tidal zone, characterized by wet-dry cycles and ion enrichment, provided optimal conditions for microbial mineralization. Notably, BSM achieved a healing efficiency of nearly 80% within 11 days, with healing products observed filling both internal and external pores. This superior performance is attributed to the enhanced metabolic activity the BS strain. Conversely, negligible healing was observed in the atmospheric zone due to insufficient moisture for bacterial activation. Micro-analyses confirmed that the healing precipitates consisted primarily of calcium carbonate crystals with minor magnesium-containing compounds. BSM shows strong adaptability in complex marine environments, offering a sustainable, sustainable solution to enhance the durability of coastal infrastructure, bolster coastal resilience, and safeguard biogenic element cycles.

Interface engineering of Si/graphene composites via compression-assisted fast joule heating for enhanced Lithium-ion battery anodes - Pengcheng Deng; Hang He; Tingting Yi; Junfeng Pan; Wenjie Liang; Beibei Yu; Zeman Xie; Zhijun Li; Danish Khan; Zeguo Tang; Xiao Yu; Dongjv Fu; et al. (Chemical Engineering Journal, 2026)

Microbial biosynthesis of fruit-like aroma compounds: Strategies and challenges toward sustainable food flavor production - Yufeng Wang; Junfeng Wu; Nan Wang; Bohai Zhang; Jianxin Dong; Yating Liu; Mingqin Zhao; Bo Fu (Food Research International, 2026)

Experimental investigation on buried pipeline bending deformation monitoring using flexible piezoelectric sensing - Jun Wang; Lipeng Wan; Kai Chen; Tong Zhang; Zhiming Liu; Zhouxia Fu; Junfeng Ni; Ziyang Gao; Hongtao Fu (Tunnelling and Underground Space Technology, 2026)

Centrifuge model study on the influence of PVD installation depth under surcharge preloading - Jun Wang; Chenglong Gu; Hongtao Fu; Long Wang; Junfeng Ni; Ziyang Gao; Xueyu Geng (Geotextiles and Geomembranes, 2026)

Hydroxysafflor yellow A from safflower enhances stress resilience and proteostasis in Caenorhabditis elegans - Linyao Jing; Zhaoxin Zhang; Zhixia Zhang; Yimeng Xu; Jing Tian; Xueqi Fu; Lan Yu; Jing Chen; Junfeng Ma (Food Research International, 2026)

Experimental study on monitoring model of bearing capacity characteristics of uplift piles based on flexible piezoelectric sensing - Jun Wang; Xinzhe Tang; Zhiming Liu; Cheng Zhang; Junfeng Ni; Ziyang Gao; Hongtao Fu; Xueyu Geng; Chaoyue Wu (Transportation Geotechnics, 2026)

Monomeric thiomolybdate ions decorated-MOFs for enhanced Hg(II) removal from water: Performance and mechanism - Chunyu Lv; Kaixing Fu; Xia Liu; Yijing Xia; Zhuoya Fang; Junfeng Zhang; Jinming Luo (Chemical Engineering Journal, 2026)

Experimental analysis of the influence of drainage board diameter coefficient on sludge treatment combining horizontal drain-vacuum preloading with geomembrane bags - Jun Wang; Chenglong Gu; Xiaobing Li; Hongtao Fu; Junfeng Ni; Ziyang Gao; Long Wang (Geotextiles and Geomembranes, 2025)

Laboratory validation of seismic damage assessment in reinforced soil models based on sensor-enabled piezoelectric geogrids (SPGG) - Jun Wang; Zhiqiang Xiang; Hongtao Fu; Yu Rao; Ziyang Gao; Junfeng Ni (Geotextiles and Geomembranes, 2025)

Stability analysis of four-phase soil-rock mixture slopes by the nodal-based continuous-discontinuous deformation analysis method combining a generalized random media reconstruction technique - Hangtian Song; Yongtao Yang; Xiaodong Fu; Yang Xia; Junfeng Li; Hong Zheng (Computers and Geotechnics, 2025)

Undrained cyclic behavior of marine soft clay considering different consolidated degrees in cyclic simple shear tests - Jun Wang; Xianjing Du; Ming Dai; Hongtao Fu; Ziyang Gao; Junfeng Ni (Soil Dynamics and Earthquake Engineering, 2025)

Rigid-flexible synergy dual-gradient microwrinkled strain sensor for machine learning-assisted wearable technology - Zhenming Chu; Luming Fu; Desheng Huang; Yuanzhi Song; Jiayi Liu; Xiaoxing Fan; Junfeng Wang; Wei Zhang (Chemical Engineering Journal, 2025)

Atmospheric Amines: Advances in Analytical Techniques, Emission Inventories, Regional Pollution, and Roles in New Particle Formation - Qi Yu; Nan Fu; Jiajia Lu; Yukai Zhang; Wei Du; Junfeng Wang (Current Pollution Reports, 2025)

Frequent horizontal transfer of AHPND-related plasmid among Vibrionaceae in the rotifers and its implication for shrimp disease management - Songzhe Fu; Ziqiang Zhang; Wenyu Zhao; Rui Wang; Junfeng Hui; Qian Yang (Aquaculture, 2025)

Aqueous production of sulfur-containing aerosols from nitroaromatic compounds and SO2 in wintertime urban haze - Ning Yang; Junfeng Wang; Daniel J. Jacob; Jianhuai Ye; Ming Sheng; Mutong Niu; Yiming Qin; Xinlei Ge; Yele Sun; Zifa Wang; Yuhang Wang; Fengchang Wu; et al. (Science Bulletin, 2025)

A global perspective on the development and application of glacio-hydrological model - Chengde Yang; Xin Wang; Shichang Kang; Min Xu; Yong Zhang; Junfeng Wei; Congsheng Fu (Journal of Hydrology, 2025)

Wide-bandgap perovskite solar cells with > 1.34 V Voc for all-perovskite tandems - Yunfei Li; Nannan Sun; Bo Feng; Wen Li; Zhengbo Cui; Wenxiao Zhang; Sheng Fu; Xiaodong Li; Junfeng Fang (Chemical Engineering Journal, 2025)

Impact of engineering geological environment on sensor-enabled piezoelectric geocable (SPGC) monitoring performance—Accelerated aging test - Yuanqiang Cai; Haokang Ying; Jun Wang; Hongtao Fu; Zhiming Liu; Junfeng Ni; Ziyang Gao (Engineering Geology, 2025)

Experimental research on geological fissure monitoring based on distributed piezoelectric sensing technology - Yuanqiang Cai; Junjie Jiang; Zhiming Liu; Jun Wang; Ziyang Gao; Hongtao Fu; Junfeng Ni (Engineering Geology, 2025)

Stubble height and irrigation significantly influenced the carbon footprint of ratoon rice cropping system in South China - Xiangyu Hu; Youqiang Fu; Nanxun Huang; Xinyu Wang; Rui Hu; Xuhua Zhong; Junfeng Pan; Meijuan Li; Yanzhuo Liu; Qunhuan Ye; Yuanhong Yin; Kaiming Liang (Field Crops Research, 2024)

Bio-accessibility and bio-availability evaluation of each arsenic species existing in various edible seaweeds in vitro and in vivo for arsenic risk assessment - Yue Lin; Junfeng Liu; Ying Sun; Shilong Chen; Jianlang Chen; FengFu Fu (Science of The Total Environment, 2024)

Enhancing Chlorella vulgaris growth with Fe-loaded sulphoaluminate cement: A promising phosphorus adsorbent reutilization strategy - Faqin Lian; Qionglin Fu; Shiyu Miao; Yanyu Zhang; Ying Wang; Junfeng Wang; Huachun Lan; Huijuan Liu; Jiuhui Qu (Resources, Conservation and Recycling, 2024)

New insight into bacterial communities of chicken manure composting under increased carbon to nitrogen ratios: Spatial heterogeneity in diversity, networks, and assembly processes - Xiaona Hu; Yangsen Jing; Nana Fu; Yongqi Wang; Dongsheng Qin; Xiaoying Guo; Yan Wang; Junfeng Wan (Journal of Environmental Chemical Engineering, 2024)

Ammonia-free selective catalytic reduction of NO by coal-based activated carbon supported Cu-Mn oxides at low temperature - Hui Fu; Junfeng Zhang; Yan Huang; Lingkui Zhao (Journal of Environmental Chemical Engineering, 2024)

Atorvastatin exerts a preventive effect against steroid-induced necrosis of the femoral head by modulating Wnt5a release - Junfeng Wu; Tao Chen; Minghang Zhang; Xing Li; Rongkun Fu; Jianzhong Xu; Andreas Nüssler; Chenxi Gu (Archives of Toxicology, 2024)

Gallic acid ameliorates synovial inflammation and fibrosis by regulating the intestinal flora and its metabolites - Junfeng Kang; Lishi Jie; Guozhen Lu; Houyu Fu; Taiyang Liao; Deren Liu; Lei Shi; Songjiang Yin; Li Zhang; Peimin Wang (Toxicology and Applied Pharmacology, 2024)

Optimization of flavonoids extracted from hawthorn （Crataegus pinnatifida） by ultrasonic-assisted deep eutectic solvent - Xiaojing Sun; Meiling Fu; Shihao Lou; Dandan Li; Xue Han; Shan Gao; Jianhua Xiu; Junfeng Wang; Yuanyuan Ren (Food Bioscience, 2024)

Enhancing the recovery of complex amino acids from excess sludge via low-intensity ultrasound-assisted enzymatic hydrolysis - Yixin Yan; Zhixuan Fu; Junfeng Wan; Yajing Zhang; Jianlei Gao; Jingqing Gao; Wei Wang (Chemical Engineering Journal, 2024)

Effect of air-boost modes on clogging behavior for vacuum consolidation with prefabricated horizontal drain - Weikai Zhang; Ziyang Gao; Junfeng Ni; Hongtao Fu; Jun Wang; Xiaobing Li; Ying Cai (Geotextiles and Geomembranes, 2024)

Ferrostatin‑1 alleviates liver injury via decreasing ferroptosis following ricin toxin poisoning in rat - Ruijiao Lin; Zijie Jia; Hongbing Chen; Hongli Xiong; Cunhao Bian; Xin He; Bi Wei; Junfeng Fu; Minzhu Zhao; Jianbo Li (Toxicology, 2024)

DNA-induced assembly of biocatalytic nanocompartments for sensitive and selective aptasensing of aflatoxin B1 - Xuan Xu; Junfeng Fu; Xiaotong Jiao; Yuqin Wang; Cheng Yao (Analytica Chimica Acta, 2024)

An Out-of-Plane Bending Fatigue Assessment Approach for Offshore Mooring Chains Considering the Real-Time Updating of Interlink Bending Stiffness - Junrong Wang; Chunlei He; Dianfu Fu; Kuang He; Junfeng Du (Journal of Marine Science and Engineering, 2024)
Fatigue failure caused by frequent tension and bending loads is a crucial safety concern for mooring chains used on floating structures in the oil and gas industry. The bending effect for a chain’s fatigue is usually not considered by existing fatigue analysis methods, and even if it is considered, existing commercial software can only calculate the constant interlink bending stiffness without consideration of the stiffness variations due to tension and friction. To address this issue, this study develops an in-plane bending (IPB)/out-of-plane bending (OPB) fatigue assessment approach for offshore mooring chains considering the time-varying nonlinear interlink bending stiffness. Initially, the mooring tension and IPB/OPB angles are calculated by an in-house code MeCAP (multi-element coupled analysis program), considering the time-varying interlink stiffness between the chain links. The fatigue life of mooring chains for pure tension–tension (TT) and OPB combined fatigue at different hotspot locations (A, B, and C) is calculated by MeCAP-fatigue, a newly-developed module in MeCAP. Based on the analysis model, a comparative study is implemented to investigate the effects of interlink stiffness on fatigue damage. The differences and advantages of the combined fatigue calculation method over the pure TT fatigue assessment method are discussed. The results illustrate that combined fatigue would be underestimated significantly if zero interlink stiffness (hinge joint assumption) is applied or even constant interlink stiffness (calculated by mooring pretension), while pure TT fatigue will be largely unaffected. Moreover, compared to pure TT fatigue, the OPB combined fatigue assessment method, considering the effects of OPB/IPB and the time-varying properties of the connection between chain links, could evaluate fatigue life more comprehensively.

Investigations of NO reduction by coal-based activated carbon with KOH activation: Performance and mechanism - Hui Fu; Junfeng Zhang; Lingkui Zhao; Yan Huang; Biao Chen (Chemosphere, 2024)

Significantly mitigating PM2.5 pollution level via reduction of NOx emission during wintertime - Shuang Fu; Pengfei Liu; Xiaowei He; Yifei Song; Junfeng Liu; Chenglong Zhang; Yujing Mu (Science of The Total Environment, 2023)

Synthesis of size-controllable, yolk-shell metal sulfide spheres for hybrid supercapacitors - Yan Zhou; Yongsheng Fu; Tingting Zhang; Chenyao Hu; Fen Qiao; Junfeng Wang; Hyuk-Jun Noh; Jong-Beom Baek (Chemical Engineering Journal, 2023)

Water grade judgment of aquaculture based on IBES and evidence fusion - Dai Junfeng; Fu Li-hui (Computers and Electronics in Agriculture, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Long-term effects of rewetting and drought on GPP in a temperate peatland based on satellite remote sensing data - Yinying Zhou; Torsten Sachs; Zhan Li; Yuwen Pang; Junfeng Xu; Aram Kalhori; Christian Wille; Xiaoxue Peng; Xianhao Fu; Yanfei Wu; Lin Wu (Science of The Total Environment, 2023)

Growth, nutrient uptake and transcriptome profiling of rice seedlings in response to mixed provision of ammonium- and nitrate-nitrogen - Youqiang Fu; Xuhua Zhong; Chusheng Lu; Kaiming Liang; Junfeng Pan; Xiangyu Hu; Rui Hu; Meijuan Li; Qunhuan Ye; Yanzhuo Liu (Journal of Plant Physiology, 2023)

Comparison of methods for detecting protein extracted from excess activated sludge - Yixin Yan; Mengnan Zhang; Jianlei Gao; Lei Qin; Xi Fu; Junfeng Wan (Environmental Science and Pollution Research, 2023)

First Asian fossil record of Platydictya (Amblystegiaceae) from the lower Miocene and its paleoenvironmental significance - Liyan Guo; Liang Xiao; Ya Li; Xiangchuan Li; Qin Leng; Nan Sun; Junfeng Guo; Chaofeng Fu; Jianan Wang; Deshuang Ji (Frontiers of Earth Science, 2023)

Evolution of the Middle Jurassic paleoclimate: Sedimentary evidence from coal-bearing strata in the Santanghu Basin, NW China - Liwei Zhang; Detian Yan; Shuguang Yang; Baoqing Li; Haijiao Fu; Gang Wang; Xiangrong Yang; Bao Zhang; Wanle Liang; Junfeng Zhang (Journal of Asian Earth Sciences, 2023)

Effect of pressurization frequency and duration on the consolidation of a dredged soil using air booster vacuum preloading combined with prefabricated horizontal drains - Jun Wang; Hongtao Fu; Weikai Zhang; Junfeng Ni; Xiaobing Li; Ying Cai (Geotextiles and Geomembranes, 2023)

A highly efficient high-entropy metal hydroxymethylate electrocatalyst for oxygen evolution reaction - Qi Jiang; Ruihu Lu; Junfeng Gu; Long Zhang; Kailong Liu; Mengyan Huang; Peng Liu; Shiyu Zuo; Yilong Wang; Yan Zhao; Peiyan Ma; Zhengyi Fu (Chemical Engineering Journal, 2023)

Efficient inverted CsPbI3 perovskite solar cells fabricated in common air - Chunyan Lu; Xiaodong Li; Xuemin Guo; Sheng Fu; Wenxiao Zhang; Haobo Yuan; Junfeng Fang (Chemical Engineering Journal, 2023)

Strength and structural variations in dredger fill subjected to vacuum dynamic consolidation - You Zhou; Hongtao Fu; Tian Jin; Mingfeng Li; Junfeng Ni (Marine Georesources & Geotechnology, 2022)

Combining targeted sequencing and ultra-low-pass whole-genome sequencing for accurate somatic copy number alteration detection - Junfeng Fu; Weihua Guo; Cheng Yan; Zhenyang Lv; Yu Wang; Ze Wang; Zhe Fan; Ting Lei (Functional & Integrative Genomics, 2021)

Artemisinin suppresses myocardial ischemia–reperfusion injury via NLRP3 inflammasome mechanism - Fengyue Wang; Qianping Gao; Jing Yang; Can Wang; Junxian Cao; Junfeng Sun; Zhixin Fan; Lu Fu (Molecular and Cellular Biochemistry, 2020)

Spatial Pattern of Female Non-agricultural Employment and Its Driving Forces in Guangdong Province, China: A Perspective of Individual and Family-level - Zhanhui Fu; Lin Mei; Yanjun Liu; Junfeng Tian; Rumin Zheng; Jing Tian (Chinese Geographical Science, 2020)

Kinetics and mechanism of diclofenac removal using ferrate(VI): roles of Fe3+, Fe2+, and Mn2+ - Junfeng Zhao; Qun Wang; Yongsheng Fu; Bo Peng; Gaofeng Zhou (Environmental Science and Pollution Research, 2018)

Decontamination of electronic waste-polluted soil by ultrasound-assisted soil washing - Fu Chen; Baodan Yang; Jing Ma; Junfeng Qu; Gangjun Liu (Environmental Science and Pollution Research, 2016)

Valosin-containing protein (VCP) promotes the growth, invasion, and metastasis of colorectal cancer through activation of STAT3 signaling - Qianfeng Fu; Yuling Jiang; Daxin Zhang; Xiuli Liu; Junfeng Guo; Jinlong Zhao (Molecular and Cellular Biochemistry, 2016)

Association of ACP1 gene polymorphisms and coronary artery disease in northeast Chinese population - TIANBAO LI; XUESONG XU; JIANZHUO LI; SHU XING; LIN ZHANG; WANNAN LI; JUNFENG MA; XUEQI FU (Journal of Genetics, 2015)